Precedence of Bone Loss Accompanied with Changes in Body Composition and Body Fat Distribution in Patients with Type 2 Diabetes Mellitus - Biao Zheng; Yuxin Zheng; Yongze Zhang; Lingning Huang; Ximei Shen; Fengying Zhao; Sunjie Yan (Journal of Diabetes Research)
Background and Objective. Diabetes and osteoporosis are common diseases in elderly people, which are often accompanied by changes in body weight during treatment. No unified conclusion has been reached on the correlation between body weight and osteoporosis yet. This study is aimed at analyzing the correlation between body composition and bone mineral density (BMD) in patients with type 2 diabetes mellitus (T2DM). Methods. A total of 596 patients with T2DM, including 308 male and 288 female patients, were included in the follow-up study; the median follow-up time was 2.17 years. We calculated the difference between the endpoint and the baseline of each body composition index and the annual rate. The research participants were divided into the increased body mass index (BMI) group, stable BMI group, and decreased BMI group. Some confounding factors were adjusted, such as BMI, fat mass index (FMI), muscle mass index (MMI), muscle/fat mass ratio (M/F), trunk fat mass index (TFMI), appendicular skeletal muscle mass index (ASMI), and appendicular skeletal muscle mass/trunk fat mass ratio (A/T). Results. The linear analysis showed that ΔFMI and ΔTFMI were negatively correlated with the change in femoral neck BMD (ΔFNBMD) and ΔMMI, ΔASMI, ΔM/F, and ΔA/T were positively correlated with ΔFNBMD. The risk of FNBMD reduction in patients with increased BMI was 56.0% lower than that in patients with decreased BMI; also, the risk in patients with stable M/F was 57.7% lower than that in patients with decreased M/F. The risk in the A/T increase group was 62.9% lower than that in the A/T decrease group. Conclusions. A reasonable muscle/fat ratio is still beneficial to maintaining bone mass. Maintaining a certain BMI value is conducive to maintaining FNBMD. Simultaneously, increasing the proportion of muscle mass and reducing fat accumulation can also prevent FNBMD loss.